2016
DOI: 10.4047/jap.2016.8.6.494
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis of splinted restoration of the most-distal implants in the posterior region

Abstract: PURPOSEThe aim of this study was to compare the efficacies of two-implant splinting (2-IS) and single-implant restoration (1-IR) in the first and second molar regions over a mean functional loading period (FLP) of 40 months, and to propose the appropriate clinical considerations for the splinting technique.MATERIALS AND METHODSThe following clinical factors were examined in the 1-IR and 2-IS groups based on the total hospital records of the patients: sex, mean age, implant location, FLP, bone grafting, clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…27,28 In contrast, the rate of mechanical complications was lower for splinted implant prostheses than for single implants. 27,28 In contrast, the rate of mechanical complications was lower for splinted implant prostheses than for single implants.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…27,28 In contrast, the rate of mechanical complications was lower for splinted implant prostheses than for single implants. 27,28 In contrast, the rate of mechanical complications was lower for splinted implant prostheses than for single implants.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have also shown that the prevalence of periimplantitis is higher in implants supporting a fixed dental prosthesis than in single implants. 27,28 In contrast, the rate of mechanical complications was lower for splinted implant prostheses than for single implants. 28 The prevalence of MBL was higher for cemented crowns than for screw-retained crowns, but there was no significant difference in the mean MBL.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…48,49 However, they may have biological weaknesses if the emergence profile and the embrasure contour are inappropriately formed. 50 In the same vein, it is known that a wider emergence angle and overcontoured prosthesis can be risk factors for peri-implantitis. 51,52 Mechanical complications occurred more often than the aforementioned biological complication.…”
Section: Insertion Torque and Isqmentioning
confidence: 99%
“…Overload may cause mechanical complication/ failure of the restoration and/or implant and biological failure of the surrounding bone. [1][2][3][4] In order to minimize those complications, some authors recommended splinting implant restorations where biomechanical risks are high, such as posterior region in an attempt to distribute the occlusal forces over a bigger resistance area. [5][6][7] A split-mouth prospective study of splinted ipsilateral implants and nonsplinted contralateral implants showed that all screw loosening complications occurred on the nonsplinted side for 5 of 15 patients.…”
Section: Introductionmentioning
confidence: 99%